PENGARUH IKLIM PSIKOLOGISTERHADAP KESIAPAN UNTUK BERUBAHPADA KARYAWAN KANTOR DIREKSI PT. PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Dwi Nursiti; Indo Mora; Sri Ramadhani; Retri Fitriyani (JURNAL PSYCHOMUTIARA, 2021)
Human resources are an important factor in a company. The psychological climate that employees experience through the company environment will have an important effect on the readiness for change that will be faced by employees. A good psychological climate that results from the corporate environment will make employees better prepared for any changes that occur. This study aims to determine the psychological influence on readiness for change in employees of PT. Perkebunan Nusantara III (Persero) Medan. This research is an influential quantitative research. The sample taken in this study is the office employees of the directors of PT. Perkebunan Nuantara III (Persero) Medan, so the sample in this study was 87 people. Based on the results of the study, it shows that R = 0.506 means that there is a relationship between the psychological climate and the readiness for change by 50.6%, which means that it has a high enough relationship. Meanwhile, R square of 0.256 means 25.6% variance of readiness for change office employees of the board of directors of PT. Perkebunan Nusantara III (Persero) Medan which was corrected by climate psychology, the rest by other factors. The aspect of perceived meaningful contribution and the aspect of management support is the aspect of the psychological climate which has a significant and positive effect on readiness to change.For the F test, the significance is 0.000 <0.05, so in accordance with the basis for decision making in the F test it can be rejected that it is accepted or in other words the simultaneous psychological climate of the readiness for change employees.